Clinical, etiological and therapeutic aspects of Dyskeratosis congenita - Perona, Rosario (2020)
The Dyskeratosis congenita corresponds to the first genetic entity described among telomeropathies, whose classic form is characterized by presenting the mucocutaneous triad of reticulated skin-lace pigmentation, nail dystrophy and oral leukoplakia. It can also occur with bone marrow failure, hematological and solid tumors, corresponding to the most serious complications. In addition to immunodeficiencies, dental, lung and liver disorders and other aspects considered minor. In turn, it presents varied genetic locus heterogeneity, with at least 14 genes involved in the telomere´s shortening, therefore associated with dyskeratosis congenita or similar phenotypes. This review discusses in addition to the clinical characteristics, the various etiological causes, evolution, available therapeutic options, and the differential diagnostic of this entity in order to provide an interdisciplinary and individualized medical evaluation that includes adequate genetic counseling.